2019
DOI: 10.1038/s41598-019-52353-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel gRNA design pipeline to develop broad-spectrum CRISPR/Cas9 gRNAs for safe targeting of the HIV-1 quasispecies in patients

Abstract: The CRISPR/Cas9 system has been proposed as a cure strategy for HIV. However, few published guide RNAs (gRNAs) are predicted to cleave the majority of HIV-1 viral quasispecies (vQS) observed within and among patients. We report the design of a novel pipeline to identify gRNAs that target HIV across a large number of infected individuals. Next generation sequencing (NGS) of LTRs from 269 HIV-1-infected samples in the Drexel CARES Cohort was used to select gRNAs with predicted broad-spectrum activity. In silico,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 92 publications
0
46
0
Order By: Relevance
“…The high genetic diversity of HIV can be another complicating factor, as even single nucleotide mismatches between the gRNA and target sequence can prevent Cas9 recognition [56]. The simultaneous use of multiple gRNAs that target highly conserved sequences seems the best strategy to circumvent this problem, although exotic HIV isolates with divergent target sequences may require specific adaptation of the gRNA molecules [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The high genetic diversity of HIV can be another complicating factor, as even single nucleotide mismatches between the gRNA and target sequence can prevent Cas9 recognition [56]. The simultaneous use of multiple gRNAs that target highly conserved sequences seems the best strategy to circumvent this problem, although exotic HIV isolates with divergent target sequences may require specific adaptation of the gRNA molecules [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The top ranked gRNAs in this region have been shown to be very effective at reducing HIV-1 transcription as we and others have previously published. 22 , 24 , 26 , 29 , 33 , 35 , 51 , 52 , 53 , 54 Effective sequence mutations and correlated functional changes in TAR implies that this low diversity region was under evolutionary constraints due to the functional importance of those sequence domains. An obvious reduction of diversity after position 615 of the LTR was due to lack of coverage for the calculation of diversity.…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent studies have designed gRNAs based on sequence conservation observed in HIV-1 sequence databases. 33 , 36 , 38 , 39 , 40 However, a conserved sequence does not guarantee a likely CRISPR-mediated cleaving site, since CRISPR possesses asymmetric tolerance for mismatches. The loss of CRISPR-mediated cleavage activity due to a single nucleotide change was quantified using gRNA mutants that targeted the same DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the Cas9 system would be more likely to bind and cleave, even though there is a mismatch. This tolerance to mismatch was used to allow investigators to design gRNAs that target more HIV viral variants ( Dampier et al, 2014 , 2016 , 2018 ; Sullivan et al, 2019 ). However, mismatch-position-based off-target prediction has raised concerns due to low predictive accuracy ( Doench et al, 2016 ).…”
Section: Target Sequence Homologymentioning
confidence: 99%